How the Cold War broke the news : the surprising roots of journalism's decline / Barbie Zelizer. - Zelizer, Barbie (Polity, 2025)
Most of us would agree that American journalism has problems. Rushed reporting and thin coverage. Timidity in the face of adversity. Polarized perspectives and euphemistic language. Groupthink about complicated events. While much blame has been levelled at big tech, Barbie Zelizer traces the decline of American journalism to the Cold War. She makes the bold claim that Cold War-era practices are to blame for the state of journalism today, undermining a once-trusted media environment. The book shows how journalism's current problems can be traced back to practices developed over half a century ago and demonstrates how they've continued to upend journalism, journalists and the news ever since.